Deux maisons, égales en dignité - Florent Kohler; Anna Greissing; François-Michel Le Tourneau (Développement Durable et Territoires)
The traditional populations of the Brazilian Amazon are subject to a double bind by institutional bodies and public opinion: these populations must preserve the forest while they act as subjects for sustainable development experiments intended to improve their living conditions and formal educational level. Two studies conducted in the State of Amapá, one in Vila Velha do Cassiporé, the other in Vila de São Francisco do Iratapuru; provide us with a few principles influencing the success or failure of these projects. These principles mainly concern community cohesion and the availability of an under-skilled workforce, which thus enable these populations to maintain activities that albeit traditional are nonetheless unpleasant.